Lethargic Infant - Thomas Noeller; Michael Smith (Association of American Medical Colleges, 2007)
Abstract In this simulation, a 10-month-old male presents via Emergency Medical Services with an altered mental status. He was found in his crib to be lethargic, hot to the touch, and difficult to arouse. Shortly after arrival in the emergency room and the primary survey, he has a generalized seizure. The case progresses through a series of decisions including seizure management, airway management, septic shock, and cardiac arrest. When this case was used in our simulation center, it was found to be an effective tool to teach and evaluate emergency medicine residents in pediatric resuscitation techniques and septic shock management. It uses a high-fidelity simulation mannequin to create a realistic atmosphere, placing residents in a high-pressure situation without risk. Standardized forms were used to successfully evaluate residents in the core competencies. Using an anonymous electronic evaluation system, excellent feedback was received from the residents who found the case to be highly educational. The case tends to flow naturally, but faculty prompting and manual transitions on the simulator may be necessary to ensure realism and smooth flow. At the end of the resuscitation, the faculty/preceptor will need to make it obvious that all further resuscitative efforts fail.